Hall–Petch Relations of Severely Deformed Cu, Ni, and Cu–Ni Alloys: Analysis of the Dislocation Blockage Strength of Deformation‐Modified Grain Boundaries. Issue 1 (30th September 2019) - Emeis, Friederike; Peterlechner, Martin; Wilde, Gerhard
Abstract : Cu–Ni alloys and pure Cu and Ni are processed by severe plastic deformation up to different selected strain levels. States of varying grain sizes and hardnesses are adjusted by selecting the total torsional strain up to saturation and subsequent thermal annealing. The hardnesses of the annealed saturation‐deformed microstructures can be described by Hall–Petch parameters valid for relaxed coarse‐grained samples. The processing conditions determine the Hall–Petch parameters in a similar way for each composition. It is concluded that relaxation and recovery modify the fine‐grained saturation‐deformed microstructures in a way that the influence of grain boundaries (GBs) on the hardness is as in a relaxed coarse‐grained microstructure. This observation also indicates that GBs and their character present in fine‐grained severe plastically deformed materials possess similar properties concerning dislocation blockage and nucleation as in a relaxed coarse‐grained microstructure. The deformation behavior of alloys and pure materials shows distinct characteristics: Alloys reach the grain size of the saturation‐deformed microstructure for smaller degrees of deformation, whereas pure materials reach saturation‐deformed hardness for smaller degrees of deformation. Thus, the dislocation and GB mobility are the dominating parameters for grain refinement and strengthening. Abstract : Cu–Ni alloys and pure Cu and Ni are severely deformed to different strains and subsequently thermally annealed. Microstructure analyses and hardness measurements indicate that grain boundaries in ultrafine‐grained materials act similar concerning dislocation blockage and nucleation as in a relaxed coarse‐grained microstructure. The dislocation and grain boundary mobilities appear to be the dominating parameters for grain refinement and strengthening.